2014
DOI: 10.1038/gene.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

The influence of polygenic risk scores on heritability of anti-CCP level in RA

Abstract: Objective To study genetic factors that influence quantitative anti-cyclic citrullinated peptide (anti-CCP) antibody levels in RA patients. Methods We carried out a genome wide association study (GWAS) meta-analysis using 1,975 anti-CCP+ RA patients from 3 large cohorts, the Brigham Rheumatoid Arthritis Sequential Study (BRASS), North American Rheumatoid Arthritis Consortium (NARAC), and the Epidemiological Investigation of RA (EIRA). We also carried out a genome-wide complex trait analysis (GCTA) to estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Twin, family, and genetic studies have shown that environmental factors make a substantial contribution, besides the genetic factors, to the development of ACPA and ACPA-positive RA [11, 19, 20]. More specifically, the risk for development of ACPA and ACPA-positive RA is associated with smoking and HLA- DRB1 gene alleles [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Twin, family, and genetic studies have shown that environmental factors make a substantial contribution, besides the genetic factors, to the development of ACPA and ACPA-positive RA [11, 19, 20]. More specifically, the risk for development of ACPA and ACPA-positive RA is associated with smoking and HLA- DRB1 gene alleles [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, some RA studies show stronger associations when the cases are limited to those with anti-cyclic citrullinated peptide antibodies (anti-CCP) [22]. However, in other studies when cases are limited to anti-CCP positive RA there are fewer susceptibility loci associated with disease, probably mostly due to decreased power as a function of a smaller sample size [23]. Similarly, if for example an SLE study was restricted to only those that manifested the same 4 out of 11 American College of Rheumatology criteria it is likely that many of the identified loci would have been missed due to weaker signals from decreased sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…RF and anti‐cyclic citrullinated peptide (anti‐CCP) antibody is an important biomarker for RA. Higher anti‐CCP levels are also associated with more active disease, more severe joint damage, worse functional disability and reduced quality of life (Ibn Yacoub et al ., ; Cui et al ., ). In this study, HLA‐SE risk alleles were strongly associated with anti‐CCP and RF level, further suggesting that HLA‐SE risk allele might be a valid indicator for predicting RA.…”
Section: Discussionmentioning
confidence: 99%